2006
DOI: 10.1159/000090498
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Inhibition of the Post-Prandial Glycaemic Response to a Standard Carbohydrate Meal following Incorporation of Alpha-Cyclodextrin

Abstract: Background: This study evaluated the dose-response effects of α-cyclodextrin, a cyclic oligosaccharide, on the glycaemic and insulinaemic responses to the consumption of a standard carbohydrate meal. Methods: In a double-blind, randomised, cross-over design, 10 healthy subjects consumed boiled white rice containing 50 g of digestible carbohydrate to which 0 (control), 2, 5 or 10 g of α-cyclodextrin was added. Plasma glucose and insulin concentrations were determined prior to and for 2 h after consumption of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 41 publications
(31 reference statements)
4
53
2
Order By: Relevance
“…Although fasting glucose did not change significantly in either group, insulin decreased by 9.5%, suggesting an increase in insulin sensitivity. A dose‐response study of α‐CD in healthy subjects demonstrated that when varying doses of α‐CD was provided in a 50 g white rice meal, 5 and 10 g doses of α‐CD reduced glucose levels 2 h postprandially compared to the control, while a 2 g dose did not show significant effects (7). In this particular study, there were no significant changes in insulin response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fasting glucose did not change significantly in either group, insulin decreased by 9.5%, suggesting an increase in insulin sensitivity. A dose‐response study of α‐CD in healthy subjects demonstrated that when varying doses of α‐CD was provided in a 50 g white rice meal, 5 and 10 g doses of α‐CD reduced glucose levels 2 h postprandially compared to the control, while a 2 g dose did not show significant effects (7). In this particular study, there were no significant changes in insulin response.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy human subjects α‐CD was able to reduce the glucose response (incremental area under the curve) to a test meal containing 50 g carbohydrate without affecting the insulin response (7). The lowered glycemic response along with the lipid binding properties of α‐CD suggest that this soluble fiber may be useful in individuals with dyslipidemia, type 2 diabetes and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In its earlier opinion (EFSA Panel on Dietetic Products Nutrition and Allergies (NDA), 2010), the Panel considered one human intervention study on the effect of alpha-cyclodextrin on post-prandial glycaemic responses (Buckley et al, 2006) and an unpublished project report which only contained the description of a study but not the results (Diamantis and Bär, 2002a). Based on the information initially provided, the Panel concluded that the evidence was insufficient to establish a cause and effect relationship between the consumption of alpha-cyclodextrin and reduction of post-prandial glycaemic responses (EFSA Panel on Dietetic Products Nutrition and Allergies (NDA), 2010).…”
Section: Scientific Substantiation Of the Claimed Effect (Id 2926)mentioning
confidence: 99%
“…In the study by Buckley et al (2006), the effects of boiled white rice with 50 g of digestible carbohydrates, to which 0, 2, 5 or 10 g of alpha-cyclodextrin were added, on post-prandial glycaemic and insulinaemic responses were investigated in 10 healthy subjects (five females), using a double-blind, randomised cross-over design. All subjects received the four test meals on a single occasion, after an overnight fast, with a wash-out period of two days.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 2926)mentioning
confidence: 99%
“…In weighing the evidence the Panel took into account that only one study was presented testing the effects of alpha-cyclodextrin on post-prandial blood glucose responses when added to white rice (Buckley et al, 2006) without accompanying evidence of a biologically plausible mechanism by which alpha-cyclodextrin could exert the claimed effect.…”
Section: Reduction Of Post-prandial Glycaemic Responses (Id 856 2926)mentioning
confidence: 99%